Inflammatory disease of the womans reproductive system: modern trends in diagnosis and therapy (literature review) - T Yu Pestrikova; I V Yurasov; E A Yurasova (IP Berlin A.V., 2018)
Medical, social and economic relevance of inflammatory diseases of the woman's reproductive organs requires a very careful attitude to the diagnosis and treatment of this pathology. The number of patients with genital infections and inflammatory diseases of the pelvic organs can takes the first place in structure of gynecological morbidity, and is 60.4-65.0%, and this fact is not unique to Russia, but all over the world. Incidence rate of inflammatory diseases of the pelvic organs in the first decade of the twenty-first century is increased at 1.4 times in patients who are from 18 to 24 years old and at 1.8 times in patients aged 25-29 years. At the same time, the cost of diagnosis and treatment has increased, reaching 50-60% of the total cost of providing gynecological care for population. The inflammatory diseases of pelvic organs are a collective concept. It includes of various nosological forms. There are numerous contradictions in the views on diagnostic approaches and treatment tactics, the nature of screening and control over the long-term results of treatment, the etiological and pathogenetic significance of various microorganisms found in the genital tract in patients with inflammatory diseases of the pelvic organs. Currently, there are many opinions among specialists about diagnostic approaches and treatment tactics, the type of screening and monitoring the long-term results of treatment, the etiological and pathogenetic role of various microorganisms which can be found in the genital tract in patients with inflammatory diseases. This review presents the results of a modern approach to the diagnosis, management and rehabilitation of patients with inflammatory diseases of the pelvic organs.